Assessing the Effects of Microfinance Services on Women's Empowerment in Pokhara, Nepal - Dhungana, Bharat Ram; Tripathi, Sushma; Chapagain, Ramkrishna; Pokhrel, Om Prakash; Saud, Hari Singh; Bhandari, Bishnu Prasad (Multi-Disciplinary Explorations: The Kasthamandap College Journal, 2024)
The subject of empowering women has become a significant issue in developing countries like Nepal. Microfinance substantially enhances women's capacity to make decisions by including them in economic activities. This research study examines the impact of microfinance services on women's empowerment. The study was conducted using a cross-sectional field survey of 150 women microfinance clients who have been taking microcredit services for at least three years. The convenient sampling technique was used to select the microfinance clients and data was collected through structured questionnaires. This study finds four explanatory variables microcredit, establishment of microbusiness, saving habit, and financial literacy have significant impact on empowering women. The study also reveals that microfinance can empower women individually, economically, and socio-politically through microcredit, micro-business, financial literacy, and savings programmes. microfinance services are an effective strategy to uplift the empowerment level of MFI clients. The regulatory authority and policymakers may promote women's empowerment through targeted microfinance interventions and capacity-building initiatives.